Bullying and Adjustment Problems in Islamic Elementary School - Agustina Setiowati, Erni (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
The number of bullying cases is getting more significant among students. The effect of bullying covers some conditions of psychology, physic, and adjustment either for bullies, bully-victims or whoever witnesses the action (bystander). The cases of bullying more problematic if the action occurs in Islamic based schools. In the Holy Quran, there are 12 verses which correlate to enmity (i’tada ya’tadi). Besides, it also has 39 verses about scolding (istahzaa yastahziu). Thus, actions relating to harassment should be decreased more than non-Islamic based schools. This study aims to describe bullying behavior and adjustment. The quantitative method is used for this study. The sample involved in this study was 73 students of Islamic elementary schools in the district of Semarang Utara selected by purposive sampling. The data were collected through a questionnaire of bullying behavior, reliability coefficient α=0.890 and corrected correlation coefficients was in the range between 0.268-0.552. SCT (Sentence Completion Test) for Children was used to measure perception of adjustment problems. Data analyzed by a descriptive statistic. The finding indicated that bullying was in a high category and students have some adjustment problems related to interpersonal relationship, in school and family, and self-concept. Kasus bullying akhir-akhir ini terus meningkat di kalangan siswa. Dampak dari bullying antara lain berpengaruh pada kondisi psikologis, fisik, dan penyesuaian baik bagi pelaku, korban, maupun teman korban atau siapapun yang menyaksikan kejadian tersebut. Kasus bullying ini lebih problematik bila terjadi di sekolah berbasis agama Islam. Dalam al-Quran terdapat 12 ayat yang berkaitan dengan kata permusuhan (i’tada ya’tadi). Disamping itu, terdapat 39 ayat mengenai cacian (ihtahzaa yastahziu). Sehingga semestinya kejadian yang berkaitan dengan kekerasan dapat ditekan dibanding pada sekolah umum. Penelitian ini bertujuan untuk mendeskripsikan perilaku bullying dan masalah penyesuaian. Sampel yang dilibatkan dalam penelitian ini adalah 73 siswa dari sekolah dasar islam di kota semarang yang dipilih menggunakan cara purposive sampling. Pengumpulan data menggunakan kuesioner perilaku bullying, reliabilitas α=0.890 dan koefisien korelasi antara skor aitem-total bergerak antara 0.268-0.552. SCT (Sentence Completion Test) untuk anak digunakan untuk mengukur persepsi terhadap masalah penyesuaian. Data dianalisis menggunakan statistik deskriptif. Hasil penelitian menunjukkan bahwa perilaku bullying pada siswa tergolong pada kategori tinggi dan terdapat beberapa masalah penyesuaian yang terkait dengan relasi interpersonal, penyesuaian di sekolah dan keluarga dan masalah konsep diri.